Perbandingan Anjak Piutang/Take Over Perspektif MUI dan SEBI pada Implementasi Bank Indonesia Melalui Perbankan Syariah - Adi Basuki Choirul; Anita Febriani (Akuisisi : Jurnal Akuntansi, 2025)
The development of the world of Islamic finance is growing rapidly in Indonesia, one of which is factoring or take over. This research was written and developed to determine the similarities and differences, as well as the concept of factoring or take over initiated by DSN-MUI and SEBI fatwas at Indonesian banks through Islamic banks. The method used is literature review with normative juridical research and observation of phenomena that occur today, which ultimately produces a conceptual paper by describing comparisons about factoring or take over systematically. The results of this study show that the concept of sharia factoring in the DSN-MUI fatwa uses wakalah bil ujrah, and the concept of Hiwalah contract in Bank Indonesia Circular Letter is the concept of debt transfer with Hiwalah muthlaqah and Hiwalah muqayyadah